Socio-economic Classification and its Scope in Crafting Rural Segments - Kakati, Rinalini Pathak; Ahmed, Shazeed (UI Scholars Hub, 2021)
With the liberalization of the Indian Economy in the mid 1990’s, substantial growth has been seen in the rural areas. Rural India which comprises around 70% of the total population of the country has become an emerging area for marketers. This study tries to identify key market variables that can help in crafting rural market segments. The socio-economic classification (SEC) 2011 which segments the market based on education level and possession of consumer durables. This study examines income as another key market variable together with education in the creation of distinct segments or hybrid segments. It then further identifies important criteria like technical, promotional and social in influencing consumers’ behaviour in the context of the purchase of consumer durables which can thereby help to create segments. The study concludes that the increase in education level has higher impact than increase in income on the important identified purchase criteria.